Green Sukuk For Sustainable Development Goals in Indonesia: A Literature Study - Ramdansyah Fitrah; Andri Soemitra (Jurnal Ilmiah Ekonomi Islam, 2022)
Realizing green economy requires extensive considerable funding, especially for renewable energy projects. This problem then encourages stakeholders to create financial instruments that focus on funding projects that are following the Sustainable Development Goals (SDGs). One of the financial instruments developed is green sukuk, an innovative form of environmentally friendly funding. The results showed that the green sector financed by sovereign green sukuk funds was following maqahid shariah in the al-kulliyah al-khamsah frame, namely guarding religion (hifdzu ad din), guarding the soul (hifdzu an Nafs), guarding reason (hifdzu aql), guarding offspring (hifdzu an nasl) and guarding property (hifdzu al Maal). The potential for green sukuk issuance can be seen from the increasing awareness of investors about the importance of environmental conservation. The involvement of influential entities such as the government and the United Nations in the development of green sukuk indicates the potential of this instrument. The challenges of issuing green sukuk include a higher risk profile because it involves high, new, and sophisticated technology. In addition, green sukuk is not a simple transaction because it involves a large number of funds, so that checks and balances are needed and proper monitoring. In order to achieve the Sustainable Development Goals, green sukuk can be used to conserve the environment and natural resources, save energy, promote the use of renewable energy and reduce the impact of greenhouse gas emissions.